2004
DOI: 10.1177/0092070303257644
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Country Bias, Country-of-Origin Effects, and Consumer Ethnocentrism: A Multidimensional Unfolding Approach

Abstract: This study uses a multidimensional unfolding approach to examine the preference patterns of U.K. consumers for domestic products and those originating from specific foreign countries for eight product categories. Results indicate that the observed variability in preferences is linked to consumer ethnocentrism. However, the latter’s capability in explaining consumer bias in favor of domestic products is dependent both on the specific country of origin and the particular product category. Implications of the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
530
7
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(617 citation statements)
references
References 62 publications
30
530
7
19
Order By: Relevance
“…Consumer ethnocentrism research asserts that consumers use domestic standards as a reference point in the evaluation of foreign products (Balabanis and Diamantopoulos, 2004). Cultural attributes, such as language, religion, social norms, and beliefs, guide consumers' preferences especially regarding consumer goods, everyday choices, and social interactions (Ghemawat, 2001).…”
Section: Country-of-origin Imagementioning
confidence: 99%
“…Consumer ethnocentrism research asserts that consumers use domestic standards as a reference point in the evaluation of foreign products (Balabanis and Diamantopoulos, 2004). Cultural attributes, such as language, religion, social norms, and beliefs, guide consumers' preferences especially regarding consumer goods, everyday choices, and social interactions (Ghemawat, 2001).…”
Section: Country-of-origin Imagementioning
confidence: 99%
“…A clustered group of Korean students might have produced somewhat different behavioural patterns of NPD consumers from general populations, and could have weakened methodological robustness because country of origin effects are said to be consumer specifi c. Specifi cally, even though a traditional study could not fi nd systematic differences between a student and a housewife sample, 46 it is suggested that a consumer sample instead of a student sample is required when a country of origin study deals with such variables correlated with age or education as consumer ethnocentrism. 47 Given, however, that the main variables of this study are purchase intentions and attitudes toward a country and college students are one of the core consumers of the NPD products, a student sample might be appropriate even though generalisation of the fi ndings of this study is limited to younger consumers. To generalise the current results, replication of this study is strongly recommended both to a national sample and to other countries.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The latter is intended to foster the reproduction of stylized facts concerning the fraction of local consumption and can be seen as a representation of differences in taste. Furthermore, there is empirical evidence suggesting a home bias in consumers choice, at least for developed countries, which can be explained by the concept of consumer ethnocentrism (see, e.g., Balabanis and Diamantopoulos, 2004;Watson and Wright, 2000). The term consumer ethnocentrism has been introduced by Shimp and Sharma (1987) to represent the responsibility and morality of purchasing foreign-made products and the loyalty of consumers to products manufactured in their home country.…”
Section: Consumption Goods Market Interactionmentioning
confidence: 99%